Framing Overtourism and Spatial Exploitation in Bali: Media Perspectives on Environmental Carrying Capacity - Putu Surya Laksana Rahjasa (International Journal Labs, 2026)
Overtourism in Bali, particularly in the regions of Badung, Denpasar, and Ubud, has become a growing concern, as it significantly impacts the environment, infrastructure, and cultural integrity of the destination. This research aims to analyze how the media frames the issue of overtourism in these regions, emphasizing spatial exploitation and environmental carrying capacity. The objective is to examine how the media highlights the environmental, social, and cultural pressures of overtourism, and how different actors—such as the government, tourism industry, and local communities are portrayed in the discourse. A qualitative approach with framing analysis was employed, using news reports from credible international and national media sources between 2023 and 2025. The findings reveal that Badung is framed as the epicentre of overtourism, with issues of congestion and pollution, while Denpasar is viewed through the lens of urbanization challenges. Ubud's framing focuses on cultural commercialization and the loss of traditional identity. The media often offers solutions such as tourism taxes, better spatial regulations, and diversifying tourism destinations to reduce pressures on the most affected areas. The study concludes by providing recommendations for sustainable tourism policies, emphasizing the importance of carrying capacity management, better spatial planning, and tourism diversification to preserve Bali's environment and cultural heritage.